Presenting New Language - Hadfield, Jill; Hadfield, Charles (Oxford Oxford University Press, 2010)
This book contains 30 activities at elementary level, all of them dealing with topics which form part of everybody's daily lives, for example families and leisure activities.
Activities ...
Contents
Keywords: Methodology; Elementary level; Classroom techniques; English - foreign language